(untitled) (Community Based Medical Journal, 2025)
Coronary artery ectasia (CAE), a rare condition characterized by abnormal dilation of the coronary arteries, has increasingly been recognized as a potential risk factor for acute myocardial infarction (AMI). While CAE is often asymptomatic, it can predispose individuals to thrombus formation, leading to occlusions and subsequent myocardial damage. Our case is a 36-year-old male with no prior medical problem who presented with chest pain and shortness of breath and was diagnosed as a non-STEMI. The coronary angiogram revealed multiple ectatic segments in the coronary artery with 100% stenosis in the circumflex branch. Coronary artery ectasia represents an emerging risk factor for acute myocardial infarction. The complex relationship between these two conditions is essential for improving diagnosis, prevention, and treatment strategies. Presentation of CAE is usually asymptomatic but when present with occlusive symptoms, management is guided by the extent of occlusion similar to coronary artery disease. CBMJ 2025 July: vol. 14 no. 02 P:193-197